APpropriAteness of percutaneous Coronary interventions in patients with ischaemic HEart disease in Italy: the APACHE pilot study. Issue 9 (5th September 2017) - Leonardi, Sergio; Marino, Marcello; Crimi, Gabriele; Maiorana, Florinda; Rizzotti, Diego; Lettieri, Corrado; Bettari, Luca; Zuccari, Marco; Sganzerla, Paolo; Tresoldi, Simone; Adamo, Marianna; Ghiringhelli, Sergio; et al.
Abstract : Objectives: To first explore in Italy appropriateness of indication, adherence to guideline recommendations and mode of selection for coronary revascularisation. Design: Retrospective, pilot study. Setting: 22 percutaneous coronary intervention (PCI)-performing hospitals (20 patients per site), 13 (59%) with on-site cardiac surgery. Participants: 440 patients who received PCI for stable coronary artery disease (CAD) or non-ST elevation acute coronary syndrome were independently selected in a 4:1 ratio with half diabetics. Primary and secondary outcome measures: Proportion of patients who received appropriate PCI using validated appropriate use scores (ie, AUS≥7). Also, in patients with stable CAD, we examined adherence to the following European Society of Cardiology recommendations: (A) per cent of patients with complex coronary anatomy treated after heart team discussion; (B) per cent of fractional flow reserve-guided PCI for borderline stenoses in patients without documented ischaemia; (C) per cent of patients receiving guideline-directed medical therapy at the time of PCI as well as use of provocative test of ischaemia according to pretest probability (PTP) of CAD. Results: Of the 401 mappable PCIs (91%), 38.7% (95% CI 33.9 to 43.6) were classified as appropriate, 47.6% (95% CI 42.7 to 52.6) as uncertain and 13.7% (95% CI 10.5% to 17.5%) as inappropriate. Median PTP in patients with stable CAD without known coronary anatomy was 69% (78% intermediate PTP, 22% high PTP). Ischaemia testing use was similar (p=0.71) in patients with intermediate (n=140, 63%) and with high PTP (n=40, 66%). In patients with stable CAD (n=352) guideline adherence to the three recommendations explored was: (A) 11%; (B) 25%; (C) 23%. AUS was higher in patients evaluated by the heart team as compared with patients who were not (7 (6.8) vs 5 (4.7); p=0.001). Conclusions: Use of heart team approaches and adherence to guideline recommendations on coronary revascularisation in a real-world setting is limited. This pilot study documents the feasibility of measuring appropriateness and guideline adherence in clinical practice and identifies substantial opportunities for quality improvement. Trial registration number: NCT02748603 .